Perfil audiométrico de usuarios con tinnitus atendidos en el Centro Ecuatoriano de Audición y Lenguaje de la ciudad de Loja durante el periodo marzo - agosto 2015. - Poma Japón, Nathaly Beatriz (2017)
The present research has as general objective to determine the audiometric profile of the tinnitus users who attend the Ecuadorian Center for Hearing and Language of the city of Loja. This study is a descriptive cross-sectional study whose universe was 300 patients and the sample was comprised of 50 users in an age between 20 and 70 years, taking into account only those who were referred by tinnitus without presenting associated otological pathologies, the same ones met the inclusion criteria. The technique used was the application of a data form, which contains information obtained from Clinical Histories with the respective audiometry of each patient, considering the classification established by the WHO (World Health Organization). In the general audiometric profile, 34% of patients with tinnitus had moderate hearing loss and 24% had mild hearing impairment. According to the prevalence criterion, 61% of the male gender corresponds to mild hearing loss, and 14% present severe hearing loss. According to the criterion of prevalence in hearing loss: 56% corresponds to the masculine gender and 44% to the feminine gender. Regarding the degree of hearing loss of each ear, the following results were identified: in the right ear 46% corresponded to mild hearing loss, and about 34% had moderate hearing loss; Of the left ear shows that 38% corresponds to mild hearing loss, about 28% present moderate hearing loss and 14% present profound hearing loss, and the age range with the highest percentage of hearing loss was found between the ages of 60 and 70 Years with 24%. The results suggest that tinnitus is associated with hearing loss and its occurrence in old age. Key words: tinnitus, audiometry, hearing loss.